2014
DOI: 10.1063/1.4890742
|View full text |Cite
|
Sign up to set email alerts
|

Gibbs ensemble Monte Carlo of nonadditive hard-sphere mixtures

Abstract: In this article, we perform Gibbs ensemble Monte Carlo (GEMC) simulations of liquid-liquid phase coexistence in nonadditive hard-sphere mixtures (NAHSMs) for different size ratios and non-additivity parameters. The simulation data are used to provide a benchmark to a number of theoretical and mixed theoretical/computer simulation approaches which have been adopted in the past to study phase equilibria in NAHSMs, including the method of the zero of the Residual Multi-Particle Entropy, Integral Equation Theories… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 51 publications
2
11
0
Order By: Relevance
“…For instance, the HNC and HNC/PY equations both cease to converge when S pp (0) ≈ 3, while S pp (0) ≈ 5 on the RY termination line. Comparing the integral-equation estimates with the Monte Carlo results, we see that the RY closure is here the most accurate, in agreement with previous studies [13,16], although it fails to converge well before the binodal. As for the RHNC, the estimates of S cc (0) and S cp (0) are consistent with the RY ones and the Monte Carlo data up to Φ p ≈ 0.08.…”
Section: B Structural Behavior In the Homogeneous Phasesupporting
confidence: 89%
See 1 more Smart Citation
“…For instance, the HNC and HNC/PY equations both cease to converge when S pp (0) ≈ 3, while S pp (0) ≈ 5 on the RY termination line. Comparing the integral-equation estimates with the Monte Carlo results, we see that the RY closure is here the most accurate, in agreement with previous studies [13,16], although it fails to converge well before the binodal. As for the RHNC, the estimates of S cc (0) and S cp (0) are consistent with the RY ones and the Monte Carlo data up to Φ p ≈ 0.08.…”
Section: B Structural Behavior In the Homogeneous Phasesupporting
confidence: 89%
“…We consider here a binary mixture of soft and hard spheres of different sizes with an intrinsic nonadditive nature. Although we take specific pair potentials, appropriate to describe, in a coarse-grained fashion, a binary system of hard-sphere colloids and long polymers under good-solvent conditions [10,11], the conclusions should apply to a general class of soft-matter systems that can be modelled as mixtures of soft and/or hard spheres, interacting via short-range potentials [12][13][14][15][16]. The phase diagram of the coarse-grained model has been accurately determined in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…The surface morphology in Figure (C) showed that the deposited film is highly crystalline and particle shapes are distinct. Such transition into crystal structure confirms the prediction made by computer simulation on structural properties and phase stability of complex fluids as a function of the deposition parameters (Abramo et al ., ; Abramo et al ., ; Pellicane & Pandaram, ). Raj et al .…”
Section: Resultsmentioning
confidence: 99%
“…Thus, making σ aa = σ c , σ bb = σ p = 0, and Δ = 1, we get σ ab = σ aa = σ cp = σ c , which is the AO model with q ≡ σ cp /σ c = (1 + Δ)/2 = 1. It is probably the simplest model exhibiting a phase separation in bulk [43] and so it also does the AO.…”
Section: Colloid-polymer Mixtures Under Confinementmentioning
confidence: 99%